Design Ethnography Epistemology and Methodology - Müller, Francis (SpringerBriefs in Anthropology, 2021)
This open access book describes methods for research on and research through design. It posits that ethnography is an appropriate method for design research because it constantly orients itself, like design projects, towards social realities. In research processes, designers acquire project-specific knowledge, which happens mostly intuitively in practice. When this knowledge becomes the subject of reflection and explication, it strengthens the discipline of design and makes it more open to interdisciplinary dialogue. Through the use of the ethnographic method in design, this book shows how design researchers can question the certainties of the everyday world, deconstruct reality into singular aesthetic and semantic phenomena, and reconfigure them into new contexts of signification. It shows that design ethnography is a process in which the epistemic and creative elements flow into one another in iterative loops. The goal of design ethnography is not to colonize the discipline of design with a positivist and objectivist scientific ethos, but rather to reinforce and reflect upon the explorative and searching methods that are inherent to it. This innovative book is of interest to design researchers and professionals, including graphic artists, ethnographers, visual anthropologists and others involved with creative arts/media.